Chronic cor pulmonale - Becerra Lanfranco, Luis (1947)
In our desire to contribute to the study of chronic Cor pulmonale, as among us has not written anything yet, this work we present the result of observation of patients who attend the outpatient clinic of the Cardiology Hospital Dos de Mayo.